PENGARUH PENGGUNAN UMPAN HIDUP DAN UMPAN PALSU PADA ALAT TANGKAP PANCING ULUR TERHADAP PENDAPATAN NELAYAN DESA SEPULU KECAMATAN SEPULU KABUPATEN BANGKALAN MADURA - Hartini, Suzana Sri; Trisbiantoro, Didik; Sumaryam, Sumaryam (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2021)
In Bangkalan Madura, many fishermen use hand-line fishing gear with live bait and fake bait, to be precise in Sepulu Village, Sepulu District and many of the catches are sold or paid to factories. By looking at developments getting better, it is interesting to study whether the effect of using live bait and fake bait on the hand-line fishing gear on fishermen's income. Fishermen who used hand-line fishing gear with live bait were sampled as many as 31 units, while fishermen who used hand-line fishing rods with fake bait were sampled as many as 33 units.Financial analysis such as capital, fixed costs, variable costs, and fixed costs incurred by handline fishermen using live bait is smaller than hand-line fishermen using fake bait. And from the statistical analysis of handline fishermen's income using live bait and fishing rods, there is a difference but not significant